PROBLEMS OF PERSONNEL MANAGEMENTOF TRADE ENTERPRISES IN THE EU - KUZMYNCHUK, Nataliia; SHUBA, Tetiana; KHOMENKO, Anastasia; PANASENKO, Ilya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Personnel management at any enterprise is a complex and multifaceted process. Managers must have deep knowledge and experience in the field of motivation, coordination, staff training, etc.,The greatest asset of any organization is its human resources, which ensure the achievement of the company's goals and objectives. It is unfortunate that most companies have neglected the development and management of their main asset, which is human resources.Human resource management is a function in an organization that focuses on hiring, managing, and shaping development directions for people who work in an organization.It is also a strategic and comprehensive approach to managing people, culture and workplace environment.Employee engagement and motivation are critical to the success of any business. Engaged employees are more productive, more committed, and more likely to stay with their employer. In today's fast-paced business environment, it is more important than ever for managers to keep their employees engaged and motivated.The importance of managing human resources lies in the fact that the most important resource of an organization is people, and that the productivity of a significant world lies among them. In order for the management of human resources to have little significant impact on the efficiency of the organization, it is necessary to expand and effectively implement the required set of policies and processes for human resources. The strategic management of human resources is the key, which is significant, as spy workers reach the goals of the organization for additional policies and practices regarding human resources, ie integration into the strategy of human resources. The growing popularity of the promotion of the mechanism of human resource management has encouraged us to do some clear exercises to improve the efficiency of the organization. There have been very few efforts to maintain a connection between the practice of effective human resource management and efficient organization, as it has been carried out in the Ukrainian economy.Today, after the pandemic, the management of the effectiveness of the glasses without precedent changes.
Keywords: sales staff; professional development; educational programs; training; company